Differentiated eliteness: socialization for academic leadership. Issue 3 (27th May 2017) - Jaffe, Alexandra
ABSTRACT: This article examines how different forms of eliteness are reflected and produced in discursive practices in texts and participant testimonials published on two websites describing American university leadership development programs. It emphasizes the way that these practices operate to thematize and differentiate forms of eliteness (academic vs. administrative) that have a long tradition of being represented as antithetical forms of knowledge, expertise and ways of life, and to socialize participants with claims to one kind of eliteness to another. Through the examination of the use of titles, characterizations of program participants as pedagogical subjects, narratives of personal transformation and "skills discourses" [Urciuoli, B. 2008. "Skills and Selves in the New Workplace." American Ethnologist 35 (2): 211–228.], the analysis shows how discourse is implicated in the production and reproduction of neoliberal subjects and perspectives on institutional functions and roles.